Pharmacoeconomic Analysis of the Use of Hepatoprotectors in Management of Drug-Associated Liver Injury Due to Hodgkin's Lymphoma Chemotherapy - D. D. Morikov; E. G. Morikova; V. V. Dvornichenko (Антибиотики и Химиотерапия, 2020)
The data on the pharmacoeconomic research of the use of Remaxol in treatment of drug-associated liver injury due to the chemotherapy in cancer patients are presented. The costs-efficiency method was applied to two groups of the patients with drug-associated liver injury treated according to different schemes. The research showed economical benefits of the Remaxol use.